Situación de los incendios forestales de vegetación nativa en la región de Valparaíso, Chile central - Castillo Soto, Miguel; Rodríguez y Silva, Francisco; Ramón Molina, Juan (Geographicalia, 2014)
Occurrence and severity are studied of forest fires in a vegetable coastal landscape of the Fifth Region of Chile, for the period 1986-2010. For this purpose an area was selected by presence of species of high scientific value, between them the forest of Jubaea chilensis (Chilean Palm), highly fragmented by the action of the fire and the urban expansion. By means of NDVI’s analysis and principal components based on information of satellite and geographical databasesof fires, it was possible to identify and to qualify areas of high sensibility, where there coexists the conflict of expansion of the cities and at the same time the continuous backward of the former native forest, in the last 25 years.
Keywords: Forest Fire; Landscape; Remote Sensing; Valparaíso (Chile)